2006
DOI: 10.1103/physrevb.73.024413
|View full text |Cite
|
Sign up to set email alerts
|

Angular dependence of exchange anisotropy on the cooling field in ferromagnet/fluoride thin films

Abstract: Exchange anisotropy in ferromagnet/antiferromagnet (FM/AF) films is usually introduced along the cooling field or FM magnetization direction. Here we investigate the dependence of the exchange anisotropy, loop bifurcation, and reversal mechanism on the cooling field direction using vector magnetometry. Three types of samples (FM=Fe, Ni /AF = FeF 2 , MnF 2 ) have been studied where the AF layer is epitaxial (110), twinned (110), and polycrystalline. With an epitaxial AF which has one spin axis, the cooling fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In general, the interfacial exchange coupling effects depend on the strength of the anisotropies 5 as well as their relative orientation, 6 exhibiting a complex phase diagram of different reversal modes. 5,6,[11][12][13][14][15] In fact, the relative orientation between the intrinsic FM anisotropy and the induced interfacial unidirectional anisotropy can be controlled by different FC procedures, varying both strength, 7,8 FC angle, 6,9,10 and/or interfacial magnetic frustration. 14,15 In this letter we present a detailed study on the magnetization reversal of FM/AFM systems with a noncollinear uniaxial, K U , and unidirectional, K E , anisotropy configuration.…”
mentioning
confidence: 99%
“…In general, the interfacial exchange coupling effects depend on the strength of the anisotropies 5 as well as their relative orientation, 6 exhibiting a complex phase diagram of different reversal modes. 5,6,[11][12][13][14][15] In fact, the relative orientation between the intrinsic FM anisotropy and the induced interfacial unidirectional anisotropy can be controlled by different FC procedures, varying both strength, 7,8 FC angle, 6,9,10 and/or interfacial magnetic frustration. 14,15 In this letter we present a detailed study on the magnetization reversal of FM/AFM systems with a noncollinear uniaxial, K U , and unidirectional, K E , anisotropy configuration.…”
mentioning
confidence: 99%
“…The Ni/FeF 2 heterostructures were deposited by electron beam evaporation onto MgF 2 (110) single-crystal substrates, with a 2 nm Al capping layer to prevent oxidation, using a base pressure of 3x10 -7 mbar, a deposition rate of 1 Ås -1 , and deposition temperatures of 300 ºC for [7,34], with crystal domains of about 30 nm [25,33]. The growth-induced easy magnetization axis of the Ni layer coincides with the AF easy axis of FeF 2 [7].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Such small crystal domains may produce a large number of pinned uncompensated spins at the boundaries which gives origin to the large EB found in these samples [6,7,34] (Figures S3 and S4, Supplemental Material). Note that our observations do not rule out the existence of individual domains with sizes below the PEEM lateral resolution of about 40 nm.…”
Section: Statistical Analysis Of the Magnetic Domainsmentioning
confidence: 95%
“…With a small misalignment ͑ϳ2°͒, the switching is clearly dominated by rotation. 17 Indeed, magnetization rotation has been clearly identified in many experimental studies and found to be a common occurrence. However, despite being prominently featured in theoretical models, 4,10 the nature of the rotations themselves has been rarely examined closely, 13 in particular, the irreversibility and the implications on the microscopic magnetization switching process.…”
mentioning
confidence: 98%
“…10,15 We have recently shown in FeF 2 and MnF 2 based systems that the switching mechanism depends on the AF crystallinity, especially on the alignment of the applied field with respect to the AF anisotropy axes. 9,16,17 For example, FM/epitaxial-FeF 2 thin films have a single AF spin axis along which the exchange field would also point. With a small misalignment ͑ϳ2°͒, the switching is clearly dominated by rotation.…”
mentioning
confidence: 99%